A typology of Inuit youth engagement in environmental research - Sadowsky, Hilary C.; Brunet, Nicolas; Anaviapik, Alex; Kublu, Abraham; Longboat, Sheri; Henri, Dominique A. (Arctic Science, 2024)
The roles of Indigenous youth in environmental research remain largely unexplored with little practical guidance for achieving meaningful engagement in environmental research. This paper aims to characterize the varying types of Inuit youth engagement in environmental research conducted in Inuit Nunangat. Findings were derived from a community-engaged participatory research approach in Mittimatalik (Pond Inlet, Nunavut). Our typology of Inuit youth engagement in environmental research suggests three types of engagements: “participate”, “conduct”, and “control”. Results highlight that Inuit youth who are interested in undertaking their own environmental research projects expect to enhance their knowledge of natural and life sciences more than those who may seek short-term supportive research roles. Strategies employed by researchers seeking to enhance youth research capacity may also vary based on youth wants and expectations. Our findings suggest that there is no one-size-fits all solution. None of the engagement types identified were necessarily and inherently considered better than the others by project contributors, unlike what has been proposed in other, hierarchical, typologies. Our proposed typology contributes to a better understanding of the varying roles that Inuit youth can play in environmental research, as well as inform potential frameworks for enhancing Inuit youth engagement and leadership in research.